EPIGENETIC and AGING - Kizil, Aslıhan; Çetin, Mehmet Emir; Ceylan, Yusuf (Bartin University, 2025)
Aging is a complex process characterized by the decline of cellular functions and the overall performance of the organism, arising from the interaction of genetic, environmental, and stochastic factors. Recent studies have demonstrated that epigenetic changes play a crucial role in the aging process. Epigenetic mechanisms, which regulate gene expression without altering the DNA sequence, shape chromatin structure and transcriptional activity, thereby playing a critical role in aging. Key epigenetic mechanisms such as DNA methylation, histone modifications, and chromatin remodeling contribute to age-associated changes in gene expression and the loss of genomic stability. Environmental stress, nutrition, caloric restriction, and lifestyle modifications can directly influence epigenetic aging. Studies conducted on model organisms have shown that caloric restriction extends lifespan by modulating epigenetic changes. Experiments in organisms such as Drosophila and C. elegans have demonstrated that genetic pathways and epigenetic modifications can extend longevity. While transposon activation leads to genomic instability in aging, certain genes have been shown to suppress this activity and provide protection against aging. Furthermore, studies on honeybee colonies and identical twins vividly illustrate the impact of epigenetic mechanisms on lifespan. In particular, the concept of the "epigenetic clock" has emerged as an important indicator in determining biological age and predicting lifespan and disease risk. The rate of epigenetic aging is associated with various diseases and phenotypes, with accelerated aging profiles observed in conditions such as smoking, obesity, HIV, and neurodegenerative disorders. Recent research has revealed that targeted interventions, including partial epigenetic reprogramming and pharmacological agents, may slow down or even reverse epigenetic aging. A better understanding of epigenetic mechanisms in aging may offer novel therapeutic strategies to promote healthy aging and extend lifespan.

Yaşlanma; genetik, çevresel ve rastlantısal faktörlerin etkileşimiyle ortaya çıkan, hücresel işlevlerin bozulması ve organizmanın genel performansının azalmasıyla karakterize edilen karmaşık bir süreçtir. Son yıllarda yapılan çalışmalar, epigenetik değişimlerin yaşlanma sürecinde rol oynadığını göstermektedir. DNA dizisini değiştirmeden gen ekspresyonunu düzenleyen epigenetik mekanizmalar, kromatin yapısını ve transkripsiyonel aktiviteyi şekillendirerek yaşlanmada kritik bir rol oynamaktadır. DNA metilasyonu, histon modifikasyonları ve kromatin yeniden düzenlenmesi gibi temel epigenetik mekanizmalar, yaşa bağlı gen ekspresyon değişikliklerine ve genomik stabilite kaybına katkıda bulunmaktadır. Çevresel stres, beslenme, kalori kısıtlaması ve yaşam tarzı değişiklikleri, epigenetik yaşlanma üzerinde doğrudan etki gösterebilmektedir. Model organizmalarla yapılan çalışmalarda, kalori kısıtlamasının epigenetik değişiklikleri düzenleyerek ömrü uzattığı gösterilmiştir. Drosophila ve C. elegans gibi organizmalarda yapılan deneyler, genetik yollar ve epigenetik modifikasyonların yaşam süresini uzatabileceğini göstermektedir. Transpozonların aktivasyonu yaşlanmada genomik kararsızlığa neden olurken, bazı genlerin bu aktiviteyi baskılayarak yaşlanmaya karşı koruma sağladığı gösterilmiştir. Ayrıca, arı kolonileri ve özdeş ikiz çalışmaları epigenetik mekanizmaların uzun ömür üzerindeki etkisini canlı şekilde ortaya koymaktadır. Özellikle “epigenetik saat” kavramı, biyolojik yaşın belirlenmesinde önemli bir gösterge haline gelmiş ve yaşam süresi ile hastalık riskleri hakkında tahmin yürütmede kullanılmaktadır. Epigenetik yaşlanma hızı, çeşitli hastalıklar ve fenotiplerle bağlantılıdır ve sigara, obezite, HIV ve nörodejeneratif hastalıklar gibi durumlarda hızlanmış yaşlanma profilleri gözlenmiştir. Son çalışmalar, kısmi epigenetik yeniden programlama ve farmakolojik ajanlar gibi hedefe yönelik müdahalelerin epigenetik yaşlanmayı yavaşlatabileceğini veya tersine çevirebileceğini ortaya koymaktadır. Yaşlanmada epigenetik mekanizmaların daha iyi anlaşılması, sağlıklı yaşlanmayı teşvik etmek ve yaşam süresini uzatmak için yeni terapötik stratejiler sunabilir.
EPİGENETİK VE YAŞLANMA
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)